Protective Effects of Chronic Intermittent Hypobaric Hypoxia Pretreatment against Aplastic Anemia through Improving the Adhesiveness and Stress of Mesenchymal Stem Cells in Rats - Jing Yang; Li Zhang; Handong Wang; Zan Guo; Yixian Liu; Yi Zhang; Chuan Wang; Quanhai Li (Stem Cells International)
Aplastic anemia (AA) is a common malignant blood disease, and chronic intermittent hypobaric hypoxia (CIHH) has a beneficial effect against different diseases. The aim of the present study was to investigate the protective effect of CIHH against AA and underlying mechanisms. 5-Fluorouracil and busulfan treatment induced AA model in rats with reduction of hematological parameters and bone marrow tissue injury and decrease of the colony numbers of progenitor cells. CIHH pretreatment significantly reduced the incidence rate of AA and alleviated above symptoms in AA model. The adhesive molecules of bone marrow mesenchymal stem cells (BMMSCs) in AA model, VLA-4, VCAM-1, and ICAM-1 were upregulated, and those of CD162 and CD164 were downregulated by CIHH pretreatment. The expressions of HIF-1α and NF-κB in BMMSCs were also decreased through CIHH pretreatment. Overall, the results demonstrated for the first time that CIHH has an anti-AA effect through improving the adhesiveness and stress of mesenchymal stem cells in rats. CIHH could be a promising and effective therapy for AA.